Comparison of three soil cultivation method in case of grape - Göblyös, J.; Zanathy, G. (International Journal of Horticultural Science, 2010)
Our results show that the different cultivation methods have effect on the yield and the grape quality as well. In 2008 and 2009 the straw mulch proved to be the best solution regarding the yield. The soil compaction was reduced in these plots and the photosintetical activity was also higher. Straw mulch could conserve the moisture content of the soil. The less yield was observed in case of barely covered vines and also the vegetative growth of the grape was less intensive in case of these vines, but it seems to be contributed to the conformation of suitable microclimate for Botrytis infection.